INFLUENCE OF INTERNATIONAL MARATHON FOZ IGUAÇU ON BONE MINERAL DENSITY AND BASAL METABOLIC RATE - A CASE STUDY. (Fiep Bulletin - online, 2013)
The marathon is one of the toughest endurance competitions, being a sporting event of mass participation, performed under variable environmental conditions. The main objective was to analyze the influence of a marathon race on bone mineral density, basal metabolic rate and body composition of an adult. It is characterized as a case study, conducted with an adult, 25 years old, male participant International Marathon Foz do Iguaçu, held on September 25, 2011, in the city of Foz do Iguaçu, Paraná, Brazil. Data were collected at the Center for Multidisciplinary Studies of Obesity (NEMO), the State University of Maringá - DEF/UEM, in the city of Maringa, Parana, Brazil. Bone mineral density was obtained by X-ray absorptiometry Dual Energy (DXA), the Basal Metabolic Rate was obtained with the analyzer VO2000 Metabolic Gases - MedGraphics measures Weight, Total Body Water (TBW), Proteins, Minerals, Body Fat Mass (BFM), Lean Muscle Mass (LMM), Body Fat Percentage (%BF) were performed with the apparatus of multifrequency bioelectrical impedance octapolar Biospace ® brand, model Inbody 520. It was observed that there was a reduction in the values ??of Body Weight, BMI, and %BF and MGC increase in TBW, Proteins, Minerals and MME. The lower limbs showed decreased levels compared to upper limbs due to the feature race. It is noteworthy reduction of 0.032 g/cm3 and 0.015 g/cm3 spine ribs, and the left side of the body most affected by race, with a reduction of 0.018 g/cm3. We conclude that marathon running causes changes in body composition, body fat distribution, increased basal metabolic rate and reduction in bone mineral content. Highlights the limitations inherent in a case study, and further studies needed for the complete elucidation of the subject.
Keywords: Marathon; Bone Mineral Density; Basal Metabolic Rate